2022
DOI: 10.3390/cancers14225640
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Thrombotic Events in Adult Patients with Acute Myeloid Leukemia: A Real-World Experience

Abstract: Information regarding the incidence and the prognostic impact of thrombotic events (TE) in non-promyelocytic acute myeloid leukemia (AML) is sparse. Although several risk factors associated with an increased risk of TE development have been recognized, we still lack universally approved guidelines for identification and management of these complications. We retrospectively analyzed 300 consecutive patients with newly diagnosed AML. Reporting the incidence of venous TE (VTE) and arterial TE (ATE) was the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The frequency of ATE in our study (2.9%) is in line with previously published data for AML (2.3%) and cancer patients (2-7%) [6][7][8][9][10][11][12][13][14]. Cancer-related studies have noted an increased risk of ATE in the period preceding cancer diagnosis as well as during the first months following diagnosis, and a quick decline thereafter [6][7][8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The frequency of ATE in our study (2.9%) is in line with previously published data for AML (2.3%) and cancer patients (2-7%) [6][7][8][9][10][11][12][13][14]. Cancer-related studies have noted an increased risk of ATE in the period preceding cancer diagnosis as well as during the first months following diagnosis, and a quick decline thereafter [6][7][8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 92%
“…Conventional cardiovascular risk factors, such as male sex, age, diabetes mellitus, hypertension, dyslipidemia, smoking, as well as a previous history of thrombosis and use of antiplatelet or anticoagulant therapy (possibly as a surrogate of pre-existing cardiovascular disease/risk), were associated with ATE in a general population and cancer patients [6][7][8][9][10][11][12]. The history of ATE had the highest association (aHR 2.96; 95% CI 2.77-3.17) [11,13]. Among our patient-related risk factors, BMI > 30, prior history of TE, presence of comorbidities and cardiovascular comorbidities as well as adverse genetic risk group were predictive for ATE in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29] Conversely, authors showed that arterial thromboses led to increased risk of early mortality and were associated with poorer overall survival. 30,31 Results of thromboembolic impact on mortality in the setting of APL are scarce. Reports by Mitrovic et al showed that both arterial and venous thromboses did not affect ED rate or 4-year overall survival.…”
Section: Impact Of Thrombosis On Early Death and Overall Survivalmentioning
confidence: 99%